Performance Evaluation of High Efficiency Particulate Filters for The Removal of Sub-Micrometer Radioactive Aerosols in Nuclear Power Reactors. Simulation Study - Djouider, Fathi (Journal of King Abdulaziz University: Engineering Sciences, 2023)
The removal of radioactive aerosols has always been one of the key issues of air decontamination in a nuclear power plant to reduce both the exposure of the radiation workers inside the NPP and environmental radiation impact. Radioactive aerosols may be removed using nuclear grade High Efficiency Particulate Air filters. The thickness of the particulate filter is function of many parameters like the particle size, the fiber diameter, the face velocity and the ratio volume of fiber/volume of filter. In this work we evaluated, by using a semi empirical model, the effect of different parameters (fiber diameter, particle size, face velocity) on the performance of the HEPA filters to reach an efficiency removal above 99.99%. The results suggest that thin layers of fiber, can work as an efficient and cost-effective filter. This study revealed that the thickness of the filter showed a positive correlation with the face velocity, but negative correlation with fiber diameter and particle diameter. It is also found that the efficiency removal is higher for lower particle velocities in air stream.